Pharmacokinetics, Pharmacodynamics, and Safety of Single Dose HSK7653 Tablets in Chinese Subjects with Normal or Impaired Renal Function - Shi, Dan; Chen, Lin; Li, Gexuan; Wu, Nan; Zhang, Fengyi; Wang, Xiaofei; Mu, Nan; Chen, Xi; Yang, Xiangyi; Lu, Jia; Lu, Yali; Wang, Meixia; et al. (Clinical pharmacokinetics, 2024)
Objective HSK7653 is a novel, ultralong-acting dipeptidyl peptidase-4 (DPP-4) inhibitor, promising for type 2 diabetes mellitus with a dosing regimen of once every 2 weeks. This trial investigates the pharmacokinetics (PKs), pharmacodynamics (PDs),and safety of HSK7653 in outpatients with normal or impaired renal function. Methods This is a multicenter, open-label, nonrandomized, parallel-controlled phase I clinical study that investigates the pharmacokinetic profiles of HSK7653 after a single oral administration in 42 subjects with mild ( n = 8), moderate ( n = 10), severe renal impairment ( n = 10), and end-stage renal disease (without dialysis, n = 5) compared with matched control subjects with normal renal function ( n = 9). Safety was evaluated throughout the study, and the pharmacodynamic effects were assessed on the basis of a DPP-4 inhibition rate. Results HSK7653 exposure levels including the maximum plasma concentration ( C max ), area under the plasma concentration–time curve from zero to last time of quantifiable concentration (AUC 0– t ), and area under the plasma concentration–time curve from zero to infinity (AUC 0–inf ) showed no significant differences related to the severity of renal impairment. Renal clearance (CL R ) showed a certain downtrend along with the severity of renal impairment. The CL R of the group with severe renal impairment and the group with end-stage renal disease were basically similar. The DPP-4 inhibition rate–time curve graph was similar among the renal function groups. All groups had favorable safety, and no serious adverse events occurred. Conclusions HSK7653 is a potent oral DPP-4 inhibitor with a long plasma half-life, supporting a dosing regimen of once every 2 weeks. Impaired renal function does not appear to impact the pharmacokinetic and pharmacodynamic properties of HSK7653 after a single administration in Chinese subjects. HSK7653 is also well tolerated without an increase in adverse events with increasing renal impairment. These results indicate that dose adjustment of HSK7653 may not be required in patients with renal impairment. Trial Registration ClinicalTrials.gov Identifier: NCT05497297.